La revue Littérama’ohi et l’émergence de la littérature polynésienne - Teata Binar (Acta Universitatis Carolinae: Philologica, 2025)
A new literature has been emerging in French Polynesia since the 1980s. The publication of the first issue of the literary magazine Littérama’ ohi: Ramées de Littérature Polynésienne, Te Hotu Ma’ ohi, in 2002 created by the indigenous Polynesian writers, testifies to the existence of Polynesian Literature. Through the selected title and subtitles of the magazine, the authors express their choices concerning their literature as to its name and to its rootedness in ma’ ohi culture. The magazine’s foreword, republished in each new issue until today, appears as a manifest, in which the authors establish the magazine’s objectives: mainly to create a “movement” among Polynesian artists and writers and enlarge the corpus of Polynesian literature. Since French Polynesia is an overseas collectivity of France, the writers have to position themselves and their writing in relation to the Francophone and post-colonial context. In their view, Polynesian literature expresses and constructs a new cultural identity that includes diverse cultural and linguistic heritage: the indigenous oral culture and the European literary tradition and culture. Polynesian literature, written mainly in French, reaches beyond national borders. It is connected with the literatures that develop in the other archipelagos of the Polynesian Triangle, for example, with Polynesian literature in English, due to the shared diasporic precolonial past. Moreover, as the ocean connects the Pacific archipelagos and oceanic peoples between them as a region, Polynesian literature can be considered at a larger scale as an Oceanian literature.